Renal Transplantation from Elderly Living Donors. (12th September 2013) - Akoh, Jacob A.; Mathuram Thiyagarajan, Umasankar
Abstract : Acceptance of elderly living kidney donors remains controversial due to the higher incidence of comorbidity and greater risk of postoperative complications. This is a review of publications in the English language between 2000 and 2013 about renal transplantation from elderly living donors to determine trends and effects of donation, and the outcomes of such transplantation. The last decade witnessed a 50% increase in living kidney donor transplants, with a disproportionate increase in donors >60 years. There is no accelerated loss of kidney function following donation, and the incidence of established renal failure (ERF) and hypertension among donors is similar to that of the general population. The overall incidence of ERF in living donors is about 0.134 per 1000 years. Elderly donors require rigorous assessment and should have a predicted glomerular filtration rate of at least 37.5 mL/min/1.73 m 2 at the age of 80. Though elderly donors had lower glomerular filtration rate before donation, proportionate decline after donation was similar in both young and elderly groups. The risks of delayed graft function, acute rejection, and graft failure in transplants from living donors >65 years are significantly higher than transplants from younger donors. A multicentred, long-term, and prospective database addressing the outcomes of kidneys from elderly living donors is recommended.